Identification of novel DNA damage response mechanisms using SLiM proteomics - Shorrocks, A-MK (2022)
The repair of damaged DNA is essential for maintaining genome integrity. Accordingly, all known forms of life have evolved a complex repertoire of biochemical pathways to detect and repair such damage, collectively called the DNA damage response. Like all biological pathways, the DNA damage response is facilitated by a series of protein-protein interactions, but the mechanisms by which DNA repair protein complexes are assembled, disassembled and regulated by post-translational modifications are still poorly understood.